Perbedaan Kinerja Keuangan Sebelum dan Saat Pandemi Covid-19 pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia - Ediningsih, Sri Isworo; Satmoko, Agung (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
Impact of the Covid-19 pandemic on companies listed on the Indonesia Stock Exchange varies widely. Some companies are trying to survive while others are experiencing a decline, and some are experiencing an increase. This study aims to determine the differences in the company's financial performance before and during the Covid-19 pandemic in food and beverage companies on the Indonesia Stock Exchange. The object of this research is 27 food and beverage companies. Wilcoxon test is used to determine differences in the company's financial performance. The test results showed that there were no differences in financial performance as measured by: CR, DR and PE before and during the Covid-19 pandemic and there were differences in financial performance: TATO and ROE before and during the Covid-19 pandemic in food and beverage companies on the Indonesia Stock Exchange.